2018
DOI: 10.1007/s10709-018-0050-y
|View full text |Cite
|
Sign up to set email alerts
|

Integrated evolution of ribosomal RNAs, introns, and intron nurseries

Abstract: The initial components of ribosomes first appeared more than 3.8 billion years ago during a time when many types of RNAs were evolving. While modern ribosomes are complex molecular machines consisting of rRNAs and proteins, they were assembled during early evolution by the association and joining of small functional RNA units. Introns may have provided the means to ligate many of these pieces together. All four classes of introns (group I, group II, spliceosomal, and archaeal) are present in many rRNA gene loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 96 publications
0
23
0
Order By: Relevance
“…Meanwhile, the origin of introns has been suggested to be ancient and could have co-evolved with rRNAs. The presence of introns in the same locations of the rRNA genes across domains of life could imply that their existence predated evolutionary divergence and speciation 33 . It has been suggested that the wide spread occurrence of the S516 intron in various eukaryotes could have arisen from vertical transfer while subsequent loss of the intron could occur later in the evolution 29 , 33 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the origin of introns has been suggested to be ancient and could have co-evolved with rRNAs. The presence of introns in the same locations of the rRNA genes across domains of life could imply that their existence predated evolutionary divergence and speciation 33 . It has been suggested that the wide spread occurrence of the S516 intron in various eukaryotes could have arisen from vertical transfer while subsequent loss of the intron could occur later in the evolution 29 , 33 .…”
Section: Discussionmentioning
confidence: 99%
“…The presence of introns in the same locations of the rRNA genes across domains of life could imply that their existence predated evolutionary divergence and speciation 33 . It has been suggested that the wide spread occurrence of the S516 intron in various eukaryotes could have arisen from vertical transfer while subsequent loss of the intron could occur later in the evolution 29 , 33 . Although intron gain and loss could occur in rRNAs, the lack of intron in all isolates bearing genotypes T4 and T5 in this study could suggest that the former process may not be common among Acanthamoeba bearing these genotypes in Thailand.…”
Section: Discussionmentioning
confidence: 99%
“…These remarkable introns, identified long ago (Michel & Dujon, ), are most frequently encoded by organellar genomes (where they were discovered) but can also be found in bacterial, archaeal, or viral genomes (Hausner, Hafez, & Edgell, ; Nawrocki, Jones, & Eddy, ) as well as in the rDNA of eukaryotic chromosomes (Johansen, Haugen, & Nielsen, ) where they might have originated (Rogers, ). Groups I and II introns form two distinct families of RNA enzymes by their 3D structures and the transesterification reactions catalysed (Adams, Stahley, Kosek, Wang, & Strobel, ; Cech, ; Pyle, ; Robart, Chan, Peters, Rajashankar, & Toor, ).…”
Section: Invasive Genetic Elementsmentioning
confidence: 99%
“…Even if the extended 5S rRNA genes are properly expressed, the insertions might not be retained in the primary transcripts in the form of expansion segments but excised as it happens with rRNA introns and intervening sequences (Rogers 2019, Evguenieva-Hackenberg 2005. The most solidly confirmed expansion segment is by far the one found in H. morrhuae 5S rRNA.…”
Section: Discussionmentioning
confidence: 99%